2022
DOI: 10.2478/johh-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Warming Vistula River – the effects of climate and local conditions on water temperature in one of the largest rivers in Europe

Abstract: The paper evaluates changes in the water temperature of the Vistula River – one of the longest rivers in Europe. Mean monthly and annual water temperatures from the period 1971–2017 for 11 stations along the entire length of the river revealed the increasing trends. The mean increase in water temperature in the analysed multi-annual period was 0.31 °C dec–1. In the majority of analysed stations, the key factor determining changes in the water temperature of the river was air temperature. The observed water war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In addition, fresh water temperature has minimum 0C, which air temperature does not have. Similar results showing an excess of water temperature over air temperature were obtained in many other works (Webb and Nobilis, 2007;Pekarova et al, 2008;Vyshnevskyi, Shevchuk, 2021;Ptak et al, 2022), but the excess in the Danube Delta is larger than in many other rivers. Importantly, water temperatures, like air temperatures, have risen essentially in recent decades.…”
Section: Water Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, fresh water temperature has minimum 0C, which air temperature does not have. Similar results showing an excess of water temperature over air temperature were obtained in many other works (Webb and Nobilis, 2007;Pekarova et al, 2008;Vyshnevskyi, Shevchuk, 2021;Ptak et al, 2022), but the excess in the Danube Delta is larger than in many other rivers. Importantly, water temperatures, like air temperatures, have risen essentially in recent decades.…”
Section: Water Temperaturesupporting
confidence: 89%
“…The conclusion about the increase in water temperature is contained in many other works (Webb and Nobilis, 2007;Basarin et al, 2016;Marszelewski and Pius, 2016;Czernecki and Ptak, 2018;Vyshnevskyi and Shevchuk, 2021;Ptak et al, 2022;Wrzesiński and Graf, 2022), but the excess of water temperature increas over air temperature increase is somewhat unusal. It can be assumed that the found feature on the Danube Delta is caused by the decrease of the river flow.…”
Section: Water Temperaturementioning
confidence: 91%
“…In particular, there are studies devoted to the thermal regime of the Vistula River. It has been identified that water temperature in the river has increased significantly in recent decades as the result of climate change (Graf & Wrzesiński, 2020;Ptak et al, 2020;Ptak et al, 2022). The same results were obtained for many European rivers and lakes (Webb et al, 2007;Adrian et al, 2009;Marszelewski & Pius, 2016;Ptak et al, 2016;Woolway et al, 2017;Lieberherr et al, 2018;Vyshnevskyi & Shevchuk, 2021;Wrzesiński & Graf, 2022;Vyshnevskyi & Shevchuk, 2023).…”
Section: Introductionsupporting
confidence: 63%
“…In order to remove the autocorrelation from the data series, a trend-free prewhitening procedure was used [39]. The adopted procedure is the most frequently used when analysing hydrological data [40,41]. This is because the method based on the Mann-Kendall and Sen test is less sensitive to extreme values compared to the linear regression method and Student's t-test.…”
Section: Procedures For Testing and Validation Of Multiple Linear Reg...mentioning
confidence: 99%